Syphilis serology in pregnancy: an eight-year study (2005–2012) in a large teaching maternity hospital in Dublin, Ireland. (March 2016) - McGettrick, Padraig; Ferguson, Wendy; Jackson, Valerie; Eogan, Maeve; Lawless, Mairead; Ciprike, Vaneta; Varughese, Alan; Coulter-Smith, Sam; Lambert, John S
All cases of positive syphilis serology detected in antenatal and peripartum screening in a large teaching maternity hospital in inner city Dublin, Ireland over an eight-year period (2005–2012 inclusive) were reviewed and included in our study. Demographic, antenatal registration, laboratory (including co-infections), partner serology, treatment and delivery data were recorded in our database. Infant follow-up, treatment and outcome data were also collected. During this period, 194 women had positive syphilis serology, of which 182 completed their pregnancies at the institution. This accounts for 0.28% of the total number of women completing their pregnancies during this time (N = 66038); 79 had no previous diagnosis of infection. There was one case of re-infection during pregnancy. Thirty-two women were co-infected with human immunodeficiency virus, hepatitis B or hepatitis C. There was one case suggestive of congenital syphilis infection. Our study is a comprehensive analysis of the diagnosis, management and clinical outcomes of women testing positive for syphilis infection in pregnancy. It reveals the relatively high prevalence of syphilis infection in the population utilising the maternity services in north inner-city Dublin. It re-enforces the importance of continued active surveillance to prevent morbidity and mortality associated with maternal syphilis infection. It also highlights the importance of strategies such as re-testing high-risk groups and definitive screening of spouse serology.